2021
DOI: 10.4103/ijo.ijo_375_21
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and optical coherence tomography changes in migraine: A comparative cross-sectional study

Abstract: Purpose: To study the prevalence of glaucoma among adults with migraine and the effect of migraine on peripapillary retinal nerve fiber layer (pRNFL) and central macular thickness (CMT) using optical coherence tomography (OCT) compared to those without migraine headache, i.e. in tension-type headache (TTH) and normal group. Methods: One hundred and eleven patients (222 eyes) were recruited in three groups. migraine, TTH, and normal subjects visiting hospital outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In addition, the PVD has been shown to be reduced in patients with normal-tension glaucoma, and the degree of reduction correlates with disease severity ( 76 ). Therefore, it is reasonable to think that the PVD reduction mediates the association between migraine and normal-tension glaucoma, which is consistent with RNFL thinning in structural OCT studies of migraine and glaucoma ( 77 ). Chronic peripapillary hypoperfusion eventually leads to RNFL atrophy and thinning.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, the PVD has been shown to be reduced in patients with normal-tension glaucoma, and the degree of reduction correlates with disease severity ( 76 ). Therefore, it is reasonable to think that the PVD reduction mediates the association between migraine and normal-tension glaucoma, which is consistent with RNFL thinning in structural OCT studies of migraine and glaucoma ( 77 ). Chronic peripapillary hypoperfusion eventually leads to RNFL atrophy and thinning.…”
Section: Discussionsupporting
confidence: 70%
“…We found 35 studies examining specifically the RNFL in migraineurs and found that studies have inconsistently shown that migraineurs have thinner RNFL than controls ( Cunha et al, 2008 ; Costello, 2009 ; Gipponi et al, 2013 ; Sorkhabi et al, 2013 ; Ekinci et al, 2014 ; Demircan et al, 2015 ; Yülek et al, 2015 ; Acer et al, 2016 ; Demirci et al, 2016 ; Feng et al, 2016 ; Verroiopoulos et al, 2016 ; Ergiyit, 2017 ; Reggio et al, 2017 ; Tunç et al, 2017 ; Abdellatif and Fouad, 2018 ; Tak et al, 2018 ; Bing et al, 2019 ; Ulusoy et al, 2019 ; You et al, 2019 ; Sirakaya et al, 2020 ; Yener and Yılmaz, 2020 ; Altunisik and Oren, 2021 ; Kanar et al, 2021 ; Panicker et al, 2021 ; Temel et al, 2021 ; Yurtoğulları et al, 2021 ), generally ipsilateral to the usual side of headache ( Martinez et al, 2008 ; Gunes et al, 2016 ; Khosravi et al, 2018 ). Lin et al examined 26 studies and also found thinner mean RNFL in migraineurs than in controls, especially in the superior and inferior eye quadrants ( Lin et al, 2021 ).…”
Section: Retinamentioning
confidence: 96%
“…Migraineurs had reduced macular retinal vessel and perfusion densities and thinner maculae than controls ( Acer et al, 2016 ; Ulusoy et al, 2019 ; Taşlı and Ersoy, 2020 ; Panicker et al, 2021 ; Yurtoğulları et al, 2021 ), especially those with more than four attacks a month ( Tunç et al, 2017 )—the more this effect was, the higher the migraine frequency and severity ( He et al, 2022 ). However, in some studies, investigators found similar macular thicknesses between all groups ( Kirbas et al, 2013 ; Demircan et al, 2015 ; Nalcacioglu et al, 2017 ; Hamurcu et al, 2021 ).…”
Section: Retinamentioning
confidence: 99%